2014
DOI: 10.5194/acp-14-11353-2014
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of new particle formation on aerosol cloud condensation nuclei (CCN) activity in Shanghai: case study

Abstract: Abstract. New particle formation (NPF) events and their impacts on cloud condensation nuclei (CCN) were investigated using continuous measurements collected in urban Shanghai from 1 to 30 April 2012. During the campaign, NPF occurred in 8 out of the 30 days and enhanced CCN number concentration (N CCN ) by a factor of 1.2-1.8, depending on supersaturation (SS). The NPF event on 3 April 2012 was chosen as an example to investigate the NPF influence on CCN activity. In this NPF event, secondary aerosols were pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 87 publications
1
29
0
Order By: Relevance
“…Observations of linearity between sulphate and nitrate in PM (2009 to 2011) Leng et al (2014a) Shanghai, CN Role of new particle formation on aerosol cloud condensation nuclei (CCN) activity (2012) Leng et al (2014b) Shanghai, CN Variations of CCN and aerosol activity during fog and haze events (2010) Makkonen et al (2014) Hyytiälä, FI Temporal cycles of NH 3 , HONO and HNO 3 at a boreal forest site (2010 to 2011) Rumsey et al (2014) North Carolina, US Performance study of the MARGA (US Environmental Protection Agency's Clean Air Status and Trends Network, CASTnet) (2010) Shi et al (2014) Shanghai, CN Investigation on PM 1 (variability, formation/dissociation, impacts on visibility) (2012) Zhou et al (2014) Shanghai, CN Measuring and modelling aerosols for haze events (2008 to 2010) a net radiometer CNR1 (Kipp&Zonen, The Netherlands) and a digital barometer (Vaisala, Germany), respectively.…”
Section: Site Description and Meteorological Parametersmentioning
confidence: 99%
“…Observations of linearity between sulphate and nitrate in PM (2009 to 2011) Leng et al (2014a) Shanghai, CN Role of new particle formation on aerosol cloud condensation nuclei (CCN) activity (2012) Leng et al (2014b) Shanghai, CN Variations of CCN and aerosol activity during fog and haze events (2010) Makkonen et al (2014) Hyytiälä, FI Temporal cycles of NH 3 , HONO and HNO 3 at a boreal forest site (2010 to 2011) Rumsey et al (2014) North Carolina, US Performance study of the MARGA (US Environmental Protection Agency's Clean Air Status and Trends Network, CASTnet) (2010) Shi et al (2014) Shanghai, CN Investigation on PM 1 (variability, formation/dissociation, impacts on visibility) (2012) Zhou et al (2014) Shanghai, CN Measuring and modelling aerosols for haze events (2008 to 2010) a net radiometer CNR1 (Kipp&Zonen, The Netherlands) and a digital barometer (Vaisala, Germany), respectively.…”
Section: Site Description and Meteorological Parametersmentioning
confidence: 99%
“…Interestingly, both PM 2.5 and PM 10 reached their peaks of 600 and 680 µg m −3 as new historic records on 6 December, approximately 14 times higher than the Grade I criteria of the National Ambient Air Quality Standard of China (50 µg m −3 for PM 10 ), and 24 times the World Health Or- (Leng et al, 2013(Leng et al, , 2014b. In addition, compared to Beijing as another megacity in China, He et al (2001), Sun et al (2004) and Liu et al (2013) .…”
Section: Particulate Mass Concentrationmentioning
confidence: 99%
“…Decreasing the height of PBL can normally hold the pollutants within the shallow surface layer, suppress the vertical atmospheric dilution and ultimately cause regional environment shrouded by pollution (Kim et al, 2007). In Shanghai, several field measurements have monitored that PBL height is usually low during hazy episodes (Leng et al, 2014b;Zhang et al, 2015). By utilizing the normalized lidar backscatter signal at 532 nm, the PBL retrieval at 30 s resolution was derived in this study, and the time-height series were plotted in red line in Fig.…”
Section: Reduction Of Pbl Heightmentioning
confidence: 99%
“…In most previous studies, the above population balance method was used to estimate new particle formation rates in China. The reported formation rates of 3 nm particles and larger ones are typically in the range of 1-10 cm −3 s −1 (Wang et al, 2013;Leng et al, 2014;An et al, 2015;Qi et al, 2015). One study in Shanghai reported a rate of 112.4 to 271.0 cm −3 s −1 for the formation of 1.5 nm particles inferred from a DEG-CPC (Xiao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In a typical NPF event, gaseous precursors burst out into particles due to nucleation and lead to a rapid increase in the atmospheric aerosol population. Nucleated particles can grow quickly to increase the number concentration of cloud condensation nuclei Kuang et al, 2009;Leng et al, 2014) and thus have indirect impacts on radiative forcing and global climate (Lohmann and Feichter, 2005). The continuous growth of nucleated particles also provides increasing aerosol surface area for heterogeneous physicochemical processes.…”
Section: Introductionmentioning
confidence: 99%